2005
DOI: 10.1507/endocrj.52.449
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Increases of Leptin and Gonadotropin-Releasing Hormone Following Exogenous Estrogen Administration in Women with Normally Menstrual Cycle

Abstract: Abstract. The aim of this study was to investigate whether administration of exogenous estrogen affects the changes of leptin and GnRH levels in women with normal menstrual cycle. A total of 18 women received a bolus intravenous injection of 20 mg conjugated estrogen (premarin group) at 0800 during the fifth day of menstrual cycle, while another 18 women were administered 20 mL of normal saline as the control group. Fasting blood samples were collected at 0,4,8, 24, 28, 32, 48, 56, 72 and 96 hours after inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Similar to the results of this study, our findings demonstrate that in obese women, leptin is directly related to FSH during the follicular phase (p < 0.001), and to testosterone in the late luteal phase (p < 0.001). Our findings lead us to concur with Lin et al [17], in their assertion that leptin must be somehow involved in the positive feedback regulation mechanism of estrogen by conveying a metabolic signal affecting the release of GnRH in hypothalamus, while its participation in the modulation of negative feedback remains unknown. However, whether or not leptin participates in the modulation of negative feedback mechanisms remains unknown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the results of this study, our findings demonstrate that in obese women, leptin is directly related to FSH during the follicular phase (p < 0.001), and to testosterone in the late luteal phase (p < 0.001). Our findings lead us to concur with Lin et al [17], in their assertion that leptin must be somehow involved in the positive feedback regulation mechanism of estrogen by conveying a metabolic signal affecting the release of GnRH in hypothalamus, while its participation in the modulation of negative feedback remains unknown. However, whether or not leptin participates in the modulation of negative feedback mechanisms remains unknown.…”
Section: Discussionsupporting
confidence: 92%
“…These investigators concluded that leptin levels change during the menstrual cycle and that leptin levels are most stable on days 1 -5 of the cycle. In another study, Lin et al [17], administrated intravenous injections of 20 mg conjugated estrogen (premarin) in 18 women with normal menstrual cycles on the fifth day of their cycle in order to evaluate whether or not estrogen affects levels of leptin and GnRH. They found that both the mean plasma levels of estrone, estradiol, were significantly increased four hours after injection and these significantly elevated levels were sustained for up to 72 hours after the injection of premarin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that leptin may be involved in the regulation of a positive feedback mechanism with estrogen as a metabolic signal that affects the release of gonadotropin-releasing hormone by the hypothalamus. 42 In an in vitro study, E 2 stimulated leptin release in women`s adipose tissue, but E 1 had no effect on leptin release. 43 Our results suggest that leptin might stimulate plasma gonadotropin-releasing hormone levels to increase, which might result in a significant positive correlation with estrogens (E 1 and E 2 ) in premenopausal women but not in postmenopausal women after adjustment for BMI.…”
Section: Discussionmentioning
confidence: 96%
“…LEPTIN is a peptide hormone that regulates energy homeostasis, reproductive functions, and immune reactions [1][2][3][4][5]. Leptin is mainly produced in the adipose tissue in non-pregnant human subjects [6][7][8] and its production is augmented by increased adiposity [6,9].…”
mentioning
confidence: 99%